Trajetória formativa: recordações de uma caminhada de vida acadêmica e profissional - Lima, Raimundo da Silva de (Brasil, 2024)
This Final Course Paper (TFC) aims to analyze the pedagogical practices developed throughout the academic training in the Bachelor's Degree in Pedagogy, offered by the National Plan for the Training of Basic Education Teachers (PARFOR) and mediated by the Federal University of Amazonas (UFAM). It is justified by the need to unite the experiences lived during the course and critically reflect on them. Using autobiography as an investigative method, the work seeks not only to report but also to analyze and understand the challenges and learning experiences faced. It concludes that critical reflection on teaching practice is fundamental for the training of more conscious and prepared teachers to face the realities of basic education in Brazil.